PREFERENSI RISIKO PETERNAK SAPI PERAH DI KECAMATAN CISARUA KABUPATEN BOGOR PROVINSI JAWA BARAT - Noviana, Rosita; Fariyanti, Anna; Winandi, Ratna (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
Cisarua District is one of the dairy farming centers with the lowest amount of milk production in Bogor Regency. The amount of milk production in Cisarua District is also known fluctuate. Differences in breeders' preferences in the use of production inputs affect production risk in dairy farming businesses. The aims of this research are to analyze the effect of production factors to production risk and risk preference of dairy farmers in Cisarua District. This research was conducted in Cisarua Subdistrict, Bogor Regency. The cross section data sourced from 91 dairy farmers were producing milk form second and third lactation cows. The model used in this research were Just and Pope model to analyze dairy farm risk production function and the Arrow-Pratt Absolute Risk Analysis model to analyze farmer's risk preferences. The results showed that forage and polar are risk reducing factors. Meanwhile, rice bran, tofu waste, concentrate, and work time are risk inducing factors in dairy farm. The risk preference of dairy farmers are risk taker to the use all of production inputs